Application of acoustoelasticity to measure the stress generated by milling in ASTM A36 steel plates - Buenos, Alexandre Aparecido; Santos Junior, Auteliano Antunes dos; Rodrigues, Alessandro Roger; Tokimatsu, Ruis Camargo [UNESP] (Abcm Brazilian Soc Mechanical Sciences & Engineering, 2013)
This work presents the study of the effects of the milling parameters on the stress field for ASTM A36 plates, using a new technique, named the ultrasonic method with acoustoelastic theory. The parameters selected are the cutting speed, the feed per tooth, and the depth of cut, which are known as the main factors to influence the residual stress fields. The stress is calculated from the time-of-flight (TOF) of critically refracted longitudinal waves. The measurements of TOF were conducted with a probe, composed of acrylic shoes and 2.25 MHz longitudinal wave transducers. The shoes were machined so the wave would reach the surface of the sample at the first critical angle. Twenty samples of low carbon hot-rolled ASTM A36 steels plates were assessed. They were heat treated for stress relief before the machining. The contribution of each milling parameter is evaluated using the design of experiments and the response surface methodology with central composite design. The parameters listed were set in five levels each, and an adequate combination of parameters and levels lead to the stress results in six selected positions of each sample. For every position, three measurements were taken each one with five replicates, thus allowing the evaluation of the dispersion. Temperature effect was accounted for and its influence was corrected. The results showed that the proposed method is sensitive to variations of the machining parameters. It allows estimating the residual stresses and shows that, for the levels selected from each parameter, the main influence comes from the depth of cut and cutting speed, and the feed per tooth does not show significant effect on the stresses.
Keywords: Nondestructive test; L-CR waves; Acoustoelasticity; Milling; Surface integrity